PENGARUH INTERVENSI COGNITIVE TRANSCENDENCE STRATEGY TERHADAP VARIABILITAS DETAK JANTUNG PENDERITA ADIKSI INTERNET PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA - Vira Monica (2023)
Introduction: The development of technology and information is increasing rapidly, one of the results of its development is the internet. The internet has negative effects of internet addiction which can affect heart rate variability. This study aims to determine the effect of the Cognitive Transcendence Strategy intervention which is a method of changing behavior by increasing cognitive abilities and spirituality on heart rate variability and internet addiction. Methods: This research is a quantitative experimental study with a Pre-experimental One Group Pretest-Posttest Design. The sample in this study amounted to 15 people who were collected by simple random sampling technique based on the criteria of the research. Results: The initial results of this study showed no difference in age, sex, internet addiction score, and heart rate variability or HRV values consisting of LF(low frequency), HF(high frequency) and TP(total power) between the treatment groups and the control group (p > 0.05). After conducting the study for seven weeks, it was found that there was a decrease in LF and an increase in HF (p> 0.05) in the treatment group. In the control group there was no difference in LF, HF, and TP after seven weeks of study. In the internet addiction score after the study for seven weeks the treatment group decreased (p < 0.05) while the control group did not decrease (p > 0.05) Conclusion: This shows that there is an effect of CTS intervention on internet addiction and changes in HRV that obtained with a decrease in sympathetic activity in subjects with internet addiction.